2016
DOI: 10.1002/2016jd025484
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the global bomb tritium transient signal with the AGCM LMDZ‐iso: A method to evaluate aspects of the hydrological cycle

Abstract: Improving the representation of the hydrological cycle in atmospheric general circulation models (AGCMs) is one of the main challenges in modeling the Earth's climate system. One way to evaluate model performance is to simulate the transport of water isotopes. Among those available, tritium is an extremely valuable tracer, because its content in the different reservoirs involved in the water cycle (stratosphere, troposphere, and ocean) varies by order of magnitude. Previous work incorporated natural tritium in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 112 publications
(131 reference statements)
4
33
1
Order By: Relevance
“…This is the reason why we restrict our analysis to the comparison of the relative variations of tritium and stable water isotopes in both snow pit profiles and model outputs. The pertinence of such a data‐model comparison is supported by the validation of stable water isotopes and tritium modeled variability (both temporally and spatially) in Antarctica with the LMDZ‐iso model (Risi et al, ; Cauquoin et al, , ). In addition, even if a straightforward comparison is limited by the chronology issue, the mean tritium level is similar in our data (Figure ) and in the modeled outputs (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the reason why we restrict our analysis to the comparison of the relative variations of tritium and stable water isotopes in both snow pit profiles and model outputs. The pertinence of such a data‐model comparison is supported by the validation of stable water isotopes and tritium modeled variability (both temporally and spatially) in Antarctica with the LMDZ‐iso model (Risi et al, ; Cauquoin et al, , ). In addition, even if a straightforward comparison is limited by the chronology issue, the mean tritium level is similar in our data (Figure ) and in the modeled outputs (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…The erroneous scheme, so-called "upstream scheme," is too diffusive (Hourdin & Armengaud, 1999) and affects all water isotopes, with as the main consequence a humid bias at the poles and especially in the polar stratosphere (Cauquoin et al, 2016;Cauquoin & Risi, 2017). As in Cauquoin et al (2016), the isotopic outputs shown here are from simulations that were nudged by the horizontal winds from 20CR reanalyzes (Compo et al, 2011). Risi et al (2010) and Cauquoin et al (2015) have shown that LMDZ-iso captures well the relative spatial variability of δ 18 O and tritium in Antarctica with (1) a decrease of δ 18 O toward low-temperature areas because of the distillation of the water mass and (2) an increase of tritium toward the East Antarctic plateau reflecting, on top of the elsewhere observed "continental effect," the strong influence of stratospheric input combined with very low humidity conditions.…”
Section: Modeled Tritium and Water Isotopes Using An Atmospheric Genementioning
confidence: 99%
“…We use here the isotopic AGCM LMDZ-iso (Risi et al, 2010a) following the model setup from Cauquoin et al (2016) at a standard latitude-longitude grid resolution of 2.5° × 3.75°, and with 39 layers in the vertical spread in a way to ensure a realistic description of the stratosphere and of the Brewer-Dobson circulation (Lott et al, 2005). The model has been validated in polar regions for the simulation of both atmospheric (Hourdin et al, 2006) and isotopic (Risi et al, 2010a) 25 variables.…”
Section: Model Simulations and Methodsmentioning
confidence: 99%
“…15 The goal of this paper is to test if the warm and enriched biases in Antarctica are associated with an excessively diffusive water vapor transport. This paper follows the work of Cauquoin et al (2016) who compare two advection schemes, which differ by their diffusive character.…”
mentioning
confidence: 99%
See 1 more Smart Citation